Mentoring Teachers during Covid-19: A Collaborative Organizational Approach - Upadhayaya, Krishna Kumari (Journal of NELTA, 2023)
Mentoring is an essential part of teacher development. It is generally acknowledged that a master talent in mentoring is the ability to make resources available to a novice protégé to help them educate successfully. This study illustrates how mentorship technique aided in boosting teacher motivation for online instruction during COVID-19. According to the research, learning is successful when there are close relationships between mentors and mentees, opportunities for growth, and a supportive atmosphere. The investigation took place in a Nepalese school in Kathmandu. Ten English Language (EL) instructors from Nursery - 10 participated in the study. They were mentored by the head of the English Department and a computer assistant for two months. The Technological Pedagogical and Content Knowledge (TPACK) model of mentoring was used, which stood on connectivism philosophy. The study employed a narrative methodology. Semi-structured interview and thematic analysis techniques were used to produce and analyse data. Standing on their stories, the teachers were familiarized with the concept of Web-Enhanced Language Learning (WELL), Mobile-Assisted Language Learning (MALL), and Computer-Assisted Language Learning (CALL). Finally, teachers produced technology enhanced lesson plans fusing the content with technology for the new pedagogy. To assess the results of mentoring during the pre-phase, while-phase, and post-phase, in-depth interviews were carried out. The ﬁndings highlight the difﬁculties mentees faced: a lack of conﬁdence or a sense of inferiority in online teaching environment, as well as how self-sufﬁciency was restored after mentoring. According to the study, effective mentorship can still take place in challenging educational circumstances.